2006
DOI: 10.1172/jci26323
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated mutations affect intracellular traffic and paracellular Mg2+ transport function of Claudin-16

Abstract: Claudin-16 (Cldn16) is selectively expressed at tight junctions (TJs) of renal epithelial cells of the thick ascending limb of Henle's loop, where it plays a central role in the reabsorption of divalent cations. Over 20 different mutations in the CLDN16 gene have been identified in patients with familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC), a disease of excessive renal Mg2+ and Ca2+ excretion. Here we show that disease-causing mutations can lead to the intracellular retention of Cld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 58 publications
4
147
0
Order By: Relevance
“…However, Ca 2ϩ transport was strikingly asymmetrical (exclusively apical-to-basal), inhibited by Mg 2ϩ , and only slightly increased above control levels, raising some doubt as to whether it was truly paracellular or specific. By contrast, Kausalya et al (57) found that claudin-16 modestly increased Mg 2ϩ permeability (P Mg ) without changing P Na , and Hou et al (44) found a marked increase in P Na with only a minor increase in P Mg . Similarly, while we have found that claudin-19, when expressed in MDCKII cells, decreases permeability to Na ϩ , Ca 2ϩ , and Mg 2ϩ (6), Hou et al (45) found that claudin-19 transfection into LLC-PK 1 cells reduced only Cl Ϫ permeability (P Cl ).…”
Section: Physiological Function Of Claudinsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, Ca 2ϩ transport was strikingly asymmetrical (exclusively apical-to-basal), inhibited by Mg 2ϩ , and only slightly increased above control levels, raising some doubt as to whether it was truly paracellular or specific. By contrast, Kausalya et al (57) found that claudin-16 modestly increased Mg 2ϩ permeability (P Mg ) without changing P Na , and Hou et al (44) found a marked increase in P Na with only a minor increase in P Mg . Similarly, while we have found that claudin-19, when expressed in MDCKII cells, decreases permeability to Na ϩ , Ca 2ϩ , and Mg 2ϩ (6), Hou et al (45) found that claudin-19 transfection into LLC-PK 1 cells reduced only Cl Ϫ permeability (P Cl ).…”
Section: Physiological Function Of Claudinsmentioning
confidence: 93%
“…At least 30 different claudin-16 mutations have now been reported in families with FHHNC (13, 56, 60, 65, 66, 76 -78, 88, 91, 94, 95, 100, 110, 111). Several are predicted to prematurely truncate the protein, and many have been shown to cause defects in trafficking of the protein to the plasma membrane (44,57,60). These findings suggested that claudin-16 might function as a divalent cation-selective paracellular pore and that FHHNC could be due to loss-of-function mutations that would be expected to abolish paracellular P Ca and P Mg in the TALH.…”
Section: Role Of Claudins In Human Diseasesmentioning
confidence: 99%
“…The gene responsible for this disease was identified by Lifton and collaborators in 1999 and named Paracellin--1 (PCLN--1) . More than 20 mutations affecting paracellin--1 trafficking or permeability have been identified up--to--date (Kausalya et al, 2006). PCLN--1 encodes for paracellin--1 (PCLN--1), also termed claudin--16.…”
Section: • Trpm7mentioning
confidence: 99%
“…SSRIs (Eller et al, 2008;O'Brien et al, 2007). Anti--inflammatory agents appear to have anti--depressant effects, as in the case of TNFα--antagonists (Uguz et al, 2009), cyclooxygenase inhibition (Muller et al, 2006) and omega--3 fatty acids .…”
Section: Neurological Function Of Magnesiummentioning
confidence: 99%
See 1 more Smart Citation